Genetic Variations of Glutathione S-Transferase Influence on Blood Cadmium Concentration - Nitchaphat Khansakorn; Waranya Wongwit; Prapin Tharnpoophasiam; Bunlue Hengprasith; Lerson Suwannathon; Suwannee Chanprasertyothin; Thunyachai Sura; Sming Kaojarern; Piyamit Sritara; Jintana Sirivarasai (Journal of Toxicology)
The glutathione S-transferases (GSTs) are involved in biotransformation and detoxification of cadmium (Cd). Genetic polymorphisms in these genes may lead to interindividual variation in Cd susceptibility. The objective of this study was to assess the association of GSTs (GSTT1, GSTM1, and GSTP1 Val105Ile) polymorphisms with blood Cd concentrations in a nonoccupationally exposed population. The 370 blood samples were analyzed for Cd concentration and polymorphisms in GSTs genes. Geometric mean of blood Cd among this population was 0.46±0.02 μg/L (with 95% CI; 0.43–0.49 μg/L). Blood Cd concentrations in subjects carrying GSTP1 Val/Val genotype were significantly higher than those with Ile/Ile and Ile/Val genotypes. No significant differences in blood Cd concentrations among individual with gene deletions of GSTT1 and GSTM1 were observed. GSTP1/GSTT1 and GSTP1/GSTM1 combinations showed significantly associated with increase in blood Cd levels. This study indicated that polymorphisms of GSTP1 combined with GSTT1 and/or GSTM1 deletion are likely to influence on individual susceptibility to cadmium toxicity.